Effect of new generation bio-regulators on anthocyanins and berry quality of grape cv. Beauty Seedless - MHETRE, V B; PATEL, V B; SINGH, S K; VERMA, M K; MISHRA, G P; DAHUJA, ANIL; KUMAR, CHAVLESH (The Indian Journal of Agricultural Sciences, 2021)
Five-year-old grapevines of Beauty Seedless spaced at 3 m × 3 m distance and trained on the 'Bower' system were sprayed with different plant bioregulators, namely, abscisic acid (ABA: 200 and 400 ppm), ethephon (200 and 400 ppm), benzothiadiazole (BTH: 0.3 and 0.6 mM), prohexadione-calcium (Pro-Ca: 200 and 400 ppm) and control (water spray) at the veraison stage during 2019-20 with the aim of studying their influence on berry physical and biochemical characteristics. The experiment was conducted in the randomised block design with three replications for each treatment. Different berry physical characteristics like weight, length, diameter and firmness were positively influenced with the different treatments except for ethephon (400 ppm) and ABA (400 ppm) treatments, which reduced the berry firmness significantly. Berry biochemical parameters were positively improved by almost all the plant bioregulators, they were most pronounced with ethephon (400 ppm) and ABA (400 ppm). The most prominent effects of ABA and ethephon treatments were noted on the total anthocyanins biosynthesis in the berries, which is major bottleneck under the warm subtropical conditions in different coloured grape genotypes. Hence, application of new generation plant bioregulators such as BTH, Pro-Ca, ABA and ethephon resulted in improvement in berry quality parameters of cv. Beauty Seedless.